Prospective Teachers’ Opinions Concerning Children’s Rights - Faiz, Melike; Kamer, Selman Tunay (Canadian Center of Science and Education, 2017)
Consideration of the child as a social being and his/her not having the power of self-protection have propounded the significance of children’s rights. Teachers are important to educate the individual. Prospective teachers who will be teachers of the future will have a considerable amount of presidency. Thus, the main objective of this research is to reveal the opinions of prospective teachers regarding children rights. Among the qualitative research methods, phenomenological research method has been adopted in this study. Among the participants of the study were 30 prospective teachers who were senior students from three different teacher education programs from a university placed in Turkey. Participants were from the departments of preschool teacher education (n=10), primary school teacher education (n=10) and social studies teacher education (n=10). Data were collected through a structured interview and analyzed by means of content analysis method. According to the findings, most prospective teachers believe that children possess differences in their educational settings, family life, economical situations and their environment that they are being raised. Hence, almost all of them stated inequality among children. Regarding implementation of child rights in the families, all prospective teachers have regarded child at an important position within the family; however, they have mentioned that families did not pay required attention to children’s right. According to prospective teachers, families should realize child as an individual, look after their rights and pay respect to children’s opinions. Furthermore, implementation of children’s rights at schools highlighted two views: The first one stress that schools are not provided required sensitivity to children’s rights, and secondly children show discipline problems in school due to limitless freeness provided for them. Regarding helping children for comprehending their rights, prospective teachers mentioned importance of reaching the large masses by means of mass media and raising the awareness of families through activities such as seminars.
Keywords: 4. Education; 10. No inequality; 16. Peace & justice